KEEFEKTIVAN MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA GENIALLY DALAM MENULIS TEKS BERITA PADA SISWA KELAS VII - Nadia Agustina; Wikanengsih; Mimin Sahmini (IKIP Siliwangi, 2026)
This study was motivated by the low writing ability of students due to the use of monotonous methods such as the lecture method. The purpose of this study is to determine the effectiveness of students' writing skills by using the Problem Based Learning (PBL) model assisted by Genially media, and the difference in the ability to write news texts in experimental and control class students. The research method used in this research is Quasy Experiment with Non-Equivalent Control Group design by examining two classes, namely experimental class and control class which are given different behaviors. The data collection technique was obtained from the Pre-Test and Post-Test test results in both the experimental and control classes. The results of this study indicate that the application of the Problem Based Learning model assisted by Genially media can improve students' news text writing ability, experiencing an increase in the value of the experimental class can be seen from the Pre-Test average value of 44.6 to 67.15 in the Post-Test value, while for the improvement of writing ability in the control class using conventional methods can be seen from the Pre-Test average value of 48.7 to 57.03 in the Post-Test value. Based on these data, the application of the Problem Based Learning model assisted by Genially media proved effective in improving the ability to write news texts in experimental class VII students.